Perancangan Desain User Interface Formulir Serah Terima Pre & Post Operasi Elektronik dengan Metode UCD - Salma Putri Rismayanti; Anton Kristijono; Nita Budiyanti (Journal of Health Information Management and Medical Record, 2025)
Healthcare facilities are required to implement Electronic Medical Records to achieve integrated medical record management. RS TK III 04.06.03 Dr. Soetarto Yogyakarta has implemented EMR, but the pre and post operative handover forms used to transfer data between treatment rooms still use manual forms, which slow down the process of searching for patient data. This study aims to design a user interface for electronic pre and post operative handover forms. This is a qualitative study with a Research and Development (R&D) design that adopts the User Centered Design (UCD) method as the design method. Data collection was conducted through interviews with five health workers who use the pre and post operative handover forms and the completion of a System Usability Scale (SUS) questionnaire to evaluate the design results. This study produced a user interface design that includes a Login Page, Dashboard Page, OK Menu Page, Pre Operative Page, Post Operative Page, Print Page, and PDF of the Pre and Post Operative Handover Form Results. The evaluation results showed an average design acceptance score of 86.5, which falls within the “Acceptable” assessment criteria with a grade scale of ‘B’ and an adjective rating of “Best Imaginable”. The results of this study indicate that the user interface design of the electronic pre and post operative handover form is acceptable and accordance with user needs.